2006
DOI: 10.1001/jama.295.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation for Severe Combined Immune Deficiency

Abstract: Our study suggests that in the absence of a relative with identical HLA, MUD BMT may provide better engraftment, immune reconstitution, and survival for patients with SCID than MMRD BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
162
5
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(179 citation statements)
references
References 36 publications
10
162
5
2
Order By: Relevance
“…Indeed, interstitial pneumonitis is the most frequent cause of death in patients who received MMRD BMT. 24,31 In contrast, we show here that on average T þ CID patients experienced only one major episode of infection or less while convalescing from MUD BMT.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Indeed, interstitial pneumonitis is the most frequent cause of death in patients who received MMRD BMT. 24,31 In contrast, we show here that on average T þ CID patients experienced only one major episode of infection or less while convalescing from MUD BMT.…”
Section: Discussioncontrasting
confidence: 63%
“…This study, which reports the largest group of patients with T þ CID to have undergone MUD BMT, reveals a survival rate of 100% using this procedure, which is superior to 77-80.5% survival reported in MUD BMT for all types of SCID. 23,24 Survival of SCID patients undergoing MMRD BMT has been reported to vary between 12.5 and 78% in single centers, while multicenter trials showed approximately 50% survival rate over the past two decades. 3,18,24,25 The survival of T þ CID in these cohorts have been estimated to be even lower.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with results we have obtained in other types of profound T-cell immunodeficiencies, 17,18 MUD transplants provided rapid engraftment and long-term robust and sustained immune function in our patients with CHH.…”
Section: Discussionsupporting
confidence: 92%
“…Human HSPC are commonly exploited for allogeneic and autologous transplantation, including GT as they have high differentiation and proliferation potential, long‐term survival capacity and self‐renewal ability 18, 21, 22, 24. They are phenotypically characterized by the absence of mature lineage markers (LIN‐) and by the expression of the CD34 molecule.…”
mentioning
confidence: 99%